Do Business Models Co-exist within a Franchise – A case study on a Scandinavian Franchise Chain - Asferg, Søren Guldbrand; Christiansen, Julie Dalbo Frost; Jensen, Charlotte Holdgård; Thomsen, Michael Henneberg (Proceedings of Pragmatic Constructivism, 2017)
This case study seeks to add new knowledge about Business Models. More precise it investigates whether different stores within a franchise have different interpretations of their Business Model. The aim is to examine whether the different stores to some extent compete against each other. A Danish optician franchise was chosen, and two different store managers and one employee were interviewed. While there were no clear indications of internal competition in the franchise, there seemed to be deviations in the concept of Business Models in the different stores. For example the stores are targeting different customer segments, they have different opinions on how to measure the performance of the employees and the two managers have different approaches on how to manage the store. It was concluded that different business models could co-exist within a franchise, and that there was not much indication of internal competition between stores.